A constituição do eu narrativo e figural na temporalidade complexa de Lobo Antunes - Stefanello, Camila (2016)
“The constitution of the narrative and figural self in the complex temporality of Lobo Antunes” has as study object the novel What horses are those that make shade on the sea? (2009), by the contemporary Portuguese writer Antonio Lobo Antunes. In the novel it is narrated the story of the affective de-structure and the loss of the material goods of a traditional Portuguese family, through the voices of family‟s components. It is confused in the narrative, thus, the past experiences of the characters and their projections for the future. The characters-narrators, when remembering the past experiences and when projecting expectations for the future, defocus the present of the narrative in reflections that seem not to finish any conclusion about their experiences. It results from that a chaotic and bitter world, marked by multiple and contradicted affections of the characters in relation to their relatives, manifesting in the own structure of the narrative, with its ramifications, deviances and fragmentations. The configuration of the intrigue ends to evince, then, the conflicting and problematic nature of the own characters. This incessant returning to the past allied to this expectative of future and the reflections about the events reconstruct these distinct moments of experience of time in a present time always distended, in transition. The novel seems to reconstruct certain aporia of time, once that the time shows itself as makeable in the consciousness of the characters, and paradoxically, as fluid and transitory. This thick and complex character of temporality in the narrative configuration, the intertwine among told present, remembered past and expected future confers a psychological density to the characters, and never attributing to them an stable and cohesive identity and an integral image. We find, thus, in this dissertation, a reflection about the contemporary Portuguese literature, the work of the author, and an analysis of the novel based, mainly, on the studies of Paul Ricoeur about the interdependence among the configuration of intrigue, temporality and the constitution of a narrative identity.